An Integrated Physical Map of the Cultivated Hot Chili Pepper, Capsicum baccatum var. Pendulum - Aguilera, Patricia Mabel (2017)
Capsicum baccatum var. Pendulum is the most frequently cultivated chili pepper in South America. This taxon is an outstanding source for breeding programs and genetic improvement in the genus, since its traits can be introgressed into C. annuum and related species to generate viable hybrids. In this study, the chromosome complement of C. baccatum var. Pendulum 2n = 24 was deeply characterized through a sequential combination of conventional and molecular cytogenetics approaches comprising Ag-NOR staining, heterochromatic fluorescence C-DAPI and CMA/DA/DAPI bandings and fluorescent in situ hybridization (FISH) of Capsicum-derived 5S and 18S-25S ribosomal genes and spacers probes. The attained markers were systematically integrated into a physical map which allows the identification of each individual chromosome. This is the first integrated physical map of C. baccatum var. Pendulum, which in conjunction with reported genetic linkage maps of Capsicum, would be useful for future high-density genetic mapping and whole-genome studies in C. baccatum and related taxa, as well as in breeding and genetic improvement programs in chili peppers